Border junkies: addiction and survival on the streets of Juárez and El Paso - Comar, Scott (Inter-America series, 2011)
Viajes -- Arrivals -- Down and out -- Assimilations -- La navidad -- New millennium -- Insanity repeats itself -- Migrations -- Vigilance -- Endings and beginnings